Agrarian Conflict Of Rempang Island Traditional Communities From A Government Communication Perspective And Political Ecology - Sinta Munawaroh; Dian Suluh Kusuma Dewi; Khoirurrosyidin; Bambang Triono (POLITICO, 2024)
This article aims to analyze the rural conflict on Rempang Island from the perspective of government communication and political ecology. Rempang Island, whose territory is rich in natural resources, is the center of tension between indigenous communities and parties interested in using land areas and natural resources. So, the political ecology approach is used to explore the impact of the agrarian conflict on Rempang Island on the indigenous communities, political forces, and the environment affected by the conflict. The occurrence of agrarian conflict in Rempang is also related to poor government communication, causing problems for indigenous communities. This research method is qualitative research using library research, data collected through research journals, online media such as news portals on websites and Twitter that are relevant to this research. The research results show that the agrarian conflict between indigenous communities on Rempang Island has had a significant impact on environmental conditions, indigenous communities and socio-political conditions in the Rempang ecological area. Moreover, communication from the government that is less than transparent results in miscommunication with indigenous communities. By understanding agrarian conflict from the perspective of government communication and political ecology, this research contributes to formulating more just and sustainable policy recommendations. Conflict resolution steps must involve the participation of indigenous communities, recognition of traditional rights, and the development of policies that pay attention to communication, ecology, and social justice.